2001
DOI: 10.1097/00006231-200109000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Post-surgical ablation of thyroid remnants with high-dose 131I in patients with differentiated thyroid carcinoma

Abstract: The aims of this study were to evaluate the efficacy of an empirically determined "fixed" high ablative dose of radioiodine ((131)I) therapy and to determine the utility of ultrasonography (US) in dose determination. A retrospective analysis was performed of 242 thyroid cancer cases treated with "fixed" high-dose (131)I for ablation of thyroid remnants without a pre-ablative (131)I diagnostic scintigraphy or radioiodine uptake study. Treatment doses ranged from 1850 MBq (50 mCi) to 7.4 GBq (200 mCi). The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…For that purpose, neck US is superior to scintigraphy and also provides information on the persistence of lymph node metastases (89,90). For this purpose, a 3-month interval is required between surgery and ultrasonographic assessment (90).…”
Section: How Are the Tissues Remaining After Surgery Quantified?mentioning
confidence: 99%
“…For that purpose, neck US is superior to scintigraphy and also provides information on the persistence of lymph node metastases (89,90). For this purpose, a 3-month interval is required between surgery and ultrasonographic assessment (90).…”
Section: How Are the Tissues Remaining After Surgery Quantified?mentioning
confidence: 99%
“…Thyroid remnant volume is one of the predictor of complete ablation (8,9). There are several ways to determine thyroid remnant volume (6).…”
Section: Discussionmentioning
confidence: 99%
“…Successful ablation depends on type of surgery, thyroid remnant volume, radioactive iodine uptake (RAIU), effective half-life (EHF) of I-131 etc (5,6). There are several studies on thyroid remnant volume and radioiodine ablation (7,8,9). Thyroid remnant can be assessed clinically or by surgeon's notes or by imaging such as ultrasonography or scintigraphy (6).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, MSD appears to be the more effi cient dosimetric method in clinical practice. However, few investigators have reported results of the MSD method [8][9][10] after it was initially proposed by Benua et al [6]. In particular, no trial of the MSD method has been conducted in patients with residual thyroid cancer who have failed conventional fi xed dose I-131 therapy.…”
Section: Introductionmentioning
confidence: 99%